Practice of emergency team in the process management of rescuing patients with acute ischemic stroke (基于急诊团队的急性缺血性脑卒中患者救治流程化管理实践) - ZUO Xia (左霞); DAI Xuemei (戴雪梅); CHEN Yueli (陈月莉) (Association of Integrative Nursing, 2021)
Objective To evaluate the practice of emergency team in the in the process management of rescuing patients with acute ischemic stroke (AIS). Methods Totally 60 AIS patients with hospital admission from January to June 2019 were included as the control group, another 58 patients with hospital admission from July to December 2019 were included as the observation group. The routine process management of emergency care was adopted in the control group, and teamwork process management was used in the observation group. The time to emergency reception, specimen delivery and laboratory test were observed, time of CT-scanning and report issuance, communication time and the door-to-needle time were observed and compared between two groups. Results After the implementation of standardized process management for AIS patients, the time of treatment indicators had been reduced, and the emergency thrombolysis compliance rate had been increased, with a significant difference(P <0. 01). Conclusion For AIS patients, the implementation of process management by the emergency team can shorten treatment time and improve treatment efficiency. (目的 探讨基于急诊团队的急性缺血性脑卒中(AIS)患者救治流程化管理的实践效果。方法 选取2019年1月-6月医院急诊科收治的60例AIS患者为对照组, 2019年7月-12月收治的58例AIS患者为观察组。对照组实施常规急救护理流程, 观察组实施基于急诊团队的急救护理流程化管理。对比2组患者急诊接诊时间、血标本送达检验科时间、实验室结果完成时间、急诊CT室检查时间、CT报告出具时间、沟通时间、入院至溶栓用药时间(DNT)时间。结果 急性缺血性脑卒中患者实施规范化流程管理诊治后, 各项指标时间均下降, 急诊溶栓达标率提升, 差异有统计学意义(P＜0. 01)。结论 基于急诊团队的流程化管理可以缩短AIS患者救治时间, 提升救治效率。)